2013
DOI: 10.1074/jbc.m112.443812
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Aspects of Hetero-oligomers Formed by the Small Heat Shock Proteins αB-Crystallin and HSP27

Abstract: Background: ␣B-crystallin and HSP27 are mammalian intracellular small heat shock proteins. Results: These proteins exchange subunits in a rapid and temperature-dependent manner. Conclusion: This facile subunit exchange suggests that differential expression could be used by the cell to regulate the response to stress. Significance: A robust technique defines parameters for the dynamic interaction between the major mammalian small heat shock proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 47 publications
(45 reference statements)
5
60
0
Order By: Relevance
“…However, this oligomer consists of both the cleaved and uncleaved proteins. It is thus likely that the two different forms of the protein cross oligomerize to form a hetero-oligomer, a phenomenon observed previously in sHSP mixtures (Studer and Narberhaus, 2000;Aquilina et al 2013). The difference in hydrodynamic radii between the homo-and hetero-oligomeric forms (5.3 and 4 nm, respectively) suggests that the oligomeric assemblies are different.…”
Section: Hsp24 Mitochondriamentioning
confidence: 80%
“…However, this oligomer consists of both the cleaved and uncleaved proteins. It is thus likely that the two different forms of the protein cross oligomerize to form a hetero-oligomer, a phenomenon observed previously in sHSP mixtures (Studer and Narberhaus, 2000;Aquilina et al 2013). The difference in hydrodynamic radii between the homo-and hetero-oligomeric forms (5.3 and 4 nm, respectively) suggests that the oligomeric assemblies are different.…”
Section: Hsp24 Mitochondriamentioning
confidence: 80%
“…Classically this includes the -crystallins of the eye lens, but numerous other vertebrate sHSPs have been indicated as coassembling [6,11]. Typically the interaction between two or more sHSPs appears to be stochastic in nature, where the representation of each component in the mixed oligomer purely reflects their input concentration [14,22]. However, a number of vertebrate sHSPs have been shown to form heterooligomers that contain a fixed ratio of the component protomers, independent of the starting proportions used [16,23].…”
Section: Discussionmentioning
confidence: 99%
“…Alone these two sHSPs are found as distinctly different assemblies. HSPB1 forms large oligomers, typically observed amongst representatives of this family of chaperones, while HSPB6 only forms dimers in solution [14,[20][21][22]. Previous studies of the heterooligomers formed between recombinant HSPB1 and HSPB6 have shown that they are considerably more polydisperse in size than the component sHSPs, with a molecular weight that spans the range between the two individual proteins [21].…”
Section: Introductionmentioning
confidence: 99%
“…and Bc [81,83]. The hetero-oligomers had masses and thermo-stabilities intermediate of the homo-oligomers and their chaperone ability was equivalent to that of αBc (and better than Hsp27).…”
mentioning
confidence: 99%